THE ROLE OF GOOGLE MEET ON THE LEARNING MEDIA OF JOURNALISTIC STUDENTS OF UIN SYARIF HIDAYATULLAH JAKARTA - Firna Nahwa Alpirdausi; Silvia Nida Sandira; Wahyunengsih (Jurnal Komunikasi dan Kebudayaan, 2022)
This study aims to describe the role of Google Meet on Journalistic Student Learning Media at UIN Syarif Hidayatullah Jakarta. The object of this research is Journalism student period 2022. The method used in this study is qualitative. Data collection techniques in this study were collected through surveys, namely using google form media. The data collection technique was carried out by asking several questions several journalism students for the 2022 period, related to the role of Google Meet in the learning media for Journalism students of UIN Syarif Hidayatullah Jakarta. Furthermore, the data that has been obtained will be discussed to determine the results of the study. The research data shows that the Google Meet application can facilitate students in the learning process, Google Meet can foster learning motivation for students, and students can repeat the material given, with the record feature in the Google Meet application. Google Meet can increase self-confidence because everyone can increase self-confidence, everyone can practice their public speaking as technology develops, and learning to be confident becomes easier because there is already an intermediary media to ask questions and give opinions.